2015
DOI: 10.1177/1045389x15595292
|View full text |Cite
|
Sign up to set email alerts
|

An optimized cross-linked network model to simulate the linear elastic material response of a smart polymer

Abstract: This article presents a novel approach to model the mechanical response of smart polymeric materials. A cyclobutanebased mechanophore, named ''smart particle'' in this article, is embedded in an epoxy polymer matrix to form the selfsensing smart material. A spring-bead model is developed based on the results from molecular dynamics simulation at the nanoscale to represent bond clusters of a smart polymer. The spring-bead network model is developed through parametric studies and mechanical equivalence optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Although biological soft tissues demonstrate viscoelastic properties [17, 2830], previous studies have found a quasi-linear material property of urological soft tissues when the stress level is under 70% of the maximal stress value [24]. Consequently, elastic material properties were used to represent mechanical behaviors of soft tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Although biological soft tissues demonstrate viscoelastic properties [17, 2830], previous studies have found a quasi-linear material property of urological soft tissues when the stress level is under 70% of the maximal stress value [24]. Consequently, elastic material properties were used to represent mechanical behaviors of soft tissues.…”
Section: Methodsmentioning
confidence: 99%
“…The joints in composite structures present a greater challenge than for homogeneous, isotopic materials since anisotropic materials do not easily accommodate stress concentrations and have intrinsic weak directions. [1][2][3][4][5] There is a higher chance of the weakest spot occurring in bonded joint. It is most common source of failure in structural laminates.…”
Section: Bonded Methodsmentioning
confidence: 99%
“…A common advantage of these composites is that certain material properties (thermal, electrical, mechanical or optical) are enhanced with minimum weight adding. [1,2,3,4,5,6]. It is of interest to investigate that how most optimized properties of the material can be reached by varying the geometry, orientation, length scale, distribution and volume fraction of the fillers.…”
Section: Introductionmentioning
confidence: 99%